Antiviral Agent Therapy Optimization in Special Populations of COVID-19 Patients - Li L; Wang X; Wang R; Hu Y; Jiang S; Lu X (Dove Medical Press, 2020)
Lu Li, Xiaojuan Wang, Rongrong Wang, Yunzhen Hu, Saiping Jiang, Xiaoyang Lu Department of Pharmacy, The First Affiliated Hospital, College of Medicine, Zhejiang University, Hangzhou, People’s Republic of ChinaCorrespondence: Xiaoyang Lu; Saiping Jiang Email luxiaoyang@zju.edu.cn; j5145@zju.edu.cnAbstract: Coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is now a global outbreak of disease. The antiviral treatment acts as one of the most important means of SARS-CoV-2 infection. Alteration of physiological characteristics in special populations may lead to the change in drug pharmacokinetics, which may result in treatment failure or increased adverse drug reactions. Some potential drugs have shown antiviral effects on SARS-CoV-2 infections, such as chloroquine, hydroxychloroquine, favipiravir, lopinavir/ritonavir, arbidol, interferon alpha, and remedsivir. Here, we reviewed the literature on clinical effects in COVID-19 patients of these antiviral agents and provided the potential antiviral agent options for pregnant women, elderly patients, liver or renal dysfunction patients, and severe or critically ill patients receiving renal replacement therapy or ECMO after SARS-CoV-2 infection.Keywords: coronavirus disease 2019, severe acute respiratory syndrome coronavirus 2, antiviral therapy, special population